Neurotized first dorsal metacarpal artery flap for reconstruction of thumb defects: does it helps to improve sensory outcomes? - Jangra, Mahesh; Parashar, Atul; Gupta, Tarush (International Surgery Journal, 2024)
Restoration of tactile sensation after reconstruction of a thumb pulp defect is important for hand function. We have evaluated the functional, sensory and aesthetic outcomes of neurotized first dorsal metacarpal artery (FDMA) flap in reconstruction of various soft tissue defects of the thumb. For a period of 18 months (January 2021 to June 2022), a total of 20 patients were considered for the study and divided into two groups that is neurotized (group A) and conventional (group B) FDMA flaps. One flap in each group underwent complete necrosis. Results were compared with patients treated by the conventional Foucher’s FDMA flap without nerve repair. At the final follow-up, flap sensation was assessed using static two-point discrimination and Semmes–Weinstein monofilament (SWM) testing. The mean values for active range of motion, total time for procedure, average time to return to routine work and time period of cortical reorientation were statistically significantly different from the values in the control group (p value <0.05). 2-PD, SWM and cold severity score were found to be statistically non-significant. Neurotized FDMA island flap provides a stable, sensate and reliable option for sensory reconstruction of thumb pulp defects with earlier cortical reorientation that allows easier physical rehabilitation and earlier ability to return to previous work to the patients.